Defining a New Femininity? Josiah Wedgwood’s Portrait Medallions of Sarah Siddons and his “Femmes Célèbres” - Patricia F. Ferguson (Yale University, 2021)
In 1788, the potter Josiah Wedgwood introduced a radical new sub-section under the banner of his popular Heads of Illustrious Moderns, from Chaucer to the Present Time focused on historical and contemporary women, rather than men, and entitled “Femmes Célèbres”. In its creation, Wedgwood celebrated the lives and achievements of twenty-eight elite, white women of immense privilege and beauty, but also objectified and commodified them for his financial gain. Within this group of aristocrats, mistresses, poets, queens, and educationalists were several female worthies, inspirational women, who possessed qualities he clearly admired—independence, intelligence, and industry. The outsider was the actress and first modern female celebrity, Sarah Siddons, whose struggles to gain acceptance by overcoming gendered obstacles paralleled those of elite, educated, literary women in their desire for recognition. Wedgwood’s gallery of female heads may have served as a visual conduct book or manual, presenting a modern vision of female agency, a new femininity that circumvented and navigated conventions of politeness and the status quo. When accompanied by enlightened conversations, even gossip, among women around the tea-table or while shopping with friends, the life choices of the sitters depicted in these portrait medallions served to educate and promote what it meant to be a woman in the late eighteenth century. This article redefines the reception of this group of ornamental portrait medallions in Wedgwood’s new stoneware bodies as decorative art objects inspired by fine art representations and made accessible through mass production.